MiR-802 participates in the inflammatory process of inflammatory bowel disease by suppressing SOCS5. Issue 4 (7th April 2020) - Yao, Jun; Gao, Ruoyu; Luo, Minghan; Li, Defeng; Guo, Liliangzi; Yu, Zichao; Xiong, Feng; Wei, Cheng; Wu, Benhua; Xu, Zhenglei; Zhang, Dingguo; Wang, Jianyao; et al.
Abstract: The present study aims to reveal the detailed molecular mechanism of microRNA (miR)-802 in the progression of inflammatory bowel disease (IBD). IBD tissues were obtained from IBD patients, followed by CD4 + cells isolation. Then, qRT-PCR and ELISA were used to detect the expression of miR-802, suppressor of cytokine signaling 5 (SOCS5), interleukin (IL)-17A and tumor necrosis factor (TNF)-α. Transfection of miR-802 mimics and miR-802 inhibitor in CD4 + cells was detected by Western blot. TargetScan and luciferase reporter assay were used to detect the relationship between SOCS5 and miR-802. Finally, colitis mice model was established to verify whether miR-802 inhibitor was involved in the protective effect of colonic mucosa. The miR-802 was highly expressed in inflamed mucosa and PBMC cells of IBD. The highest expression of miR-802 was observed in CD4 + T cells based on different immune cell subsets analysis. SOCS5 was the target gene of miR-802. The mice model experiments showed that blockade of miR-802 could alleviate mice colitis. Our study suggests that up-regulation of miR-802 plays an important role in inflammatory process of IBD via targeting SOCS5. Moreover, the differentiation of Th17 and secretion of TNF-α in IBD could be stimulated by miR-802.